Estrogen/Progesterone Receptor Loss, CTNNB1 and KRAS Mutations Are Associated With Local Recurrence or Distant Metastasis in Low-Grade Endometrial Endometrioid Carcinoma. Issue 3 (26th March 2023) - Chibbar, Rajni; Foerstner, Sabrina; Suresh, Janarathnee; Chibbar, Richa; Piche, Alexandre; Kundapur, Deeksha; Kanthan, Rani; Kundapur, Vijayanand; Lee, Cheng Han; Agrawal, Anita; Lai, Raymond
Abstract : A subset of endometrial endometrioid carcinomas (EECs) with low-grade histology recur with poor outcomes. Published evidence suggests that poor outcomes may be associated with loss of expression of ER-alpha (ER-α) as well as with β-Catenin-1 ( CTNNB1 ) and Kirsten rat sarcoma viral oncogene homolog ( KRAS ) mutations. This study reports on institutional experience with the incidence of recurrence in low-grade EEC and their association with CTNNB1 and KRAS mutations as well as estrogen/progesterone receptor (ER/PR) expression. Forty-eight (8.5%) out of 568 cases of low-grade EEC with biopsy-proven recurrence were identified; and were analyzed by immunohistochemistry for ER, PR, p53, MMR protein, and mutation analysis for exon 3 of the CTNNB1 and exon 2 of KRAS in relation to recurrence type, local or distant metastasis/recurrence. Twenty-three patients (4%) developed local, and 25 patients (4.4%) developed distant metastases/recurrence. Decreased expression or loss of ER/PR was found in 17/44 (38.6%) patients with recurrence. Eighty-four percent of patients with low-grade EEC and local recurrence had CTNNB1 mutations. Seventy-three percent of patients with distant metastasis/recurrence had KRAS mutations. The association of these mutations with the type of recurrence was statistically significant for both. Five cases with the morphology of low-grade EEC were reclassified as mesonephric-like carcinoma and were universally characterized by distant metastasis/recurrence, loss of ER/PR expression, large tumor size, absence of CTNNB1 mutations, and the presence of KRAS mutations. In low-grade EEC, CTNNB1 and KRAS mutations are associated with local recurrence and distant metastasis/recurrence, respectively, suggesting that these 2 different progression types may be conditioned by tumor genotype. ER/PR immunohistochemistry may be helpful in identifying poor performers in low-grade EEC. Furthermore, identification of the decreased expression or loss of ER/PR in tumors with low-grade histology should prompt consideration of mesonephric-like carcinoma, which is a more aggressive tumor than the low-grade EEC. KRAS mutations were associated with distant metastasis/recurrence in tumors with and without mesonephric-like phenotype.